'Becoming others': Valuing our relationship and communication with students. (3rd July 2017) - Chanda-Gool, Sofia; Mamas, Christoforos
Abstract: This paper reviews a qualitative study of student and lecturer communication and engagement within a 'safe', 'structured' setting. Relationships between students and academics are part of an emotional as well as intellectual encounter. Our sense of self is profoundly affected by how we feel others think about us. Being heard and valued gives us the confidence to question. Yet within the university context hierarchies and positions easily inhibit this rich potential. The prevalent focus on performativity and individual success can undermine our shared encounters, isolating us so that group work, endemic within university processes becomes, tokenistic and superficial. The study embedded 'selves' within a small group setting that facilitated a sense of belonging, open mindedness and compassion towards others by sharing thoughts and experiences. Students and academics exchanged roles and responsibilities. The results suggest that if this type of group work was extended and implemented into the wider university practice, certain concerns about inclusion and equity could be addressed and students and lecturers could enjoy a deeper intellectual and emotional affinity.